Innovating Bureaucracy for a More Capable Government - World Bank Group (World Bank, Washington, DC, 2019)
Improving government capability is one of the main challenges of economic development. There is consensus around the core policies needed for developing countries to achieve equitable growthand reduce extreme poverty. But government capability—its ability to effectively implement these polices and efficiently achieve the desired outputs in regulation, infrastructure provision, and service delivery—varies considerably across countries and across policy domains within countries.The ability, motivation, and productivity of the personnel who populate government bureaucracies are key determinants of government capability. Capable organizations are those that can select high-ability personnel, provide them with the necessary resources, and motivate them to work toward the organization’s objectives and to serve the public. In Russia, 60 percent of the price variation in standard procurement contracts is due to the ability of individual bureaucrats andthe quality of the organizations in which they work. If the worst-performing 20 percent of bureaucrats can be made as effective as the median bureaucrat, the Russian government would save 10 percent of its procurement costs. In Nigeria, there is substantial variation in the quality of organizational management across the federal government, and a one standard deviation increase in the quality of management would lead to a 32 percent increase in project completion rates. Public sector compensation and employment practices also have significant implications for the competitiveness of the overall labor market, and on fiscal sustainability. Governments face important choices relating to the size of the public sector and the compensation of its workers. Low public sector wages can result in difficulties in recruiting and retaining qualified workers; but large wage premiums for public sector workers can discourage private sector jobs and lead to search unemployment. A rising wage bill is also often associated with problems of fiscal sustainability. The report focuses primarily on the supply side of governance and does not delve into the political economy of public administration, for both conceptual and methodological reasons. The domain of citizen engagement is largely at the point of service delivery or revenue collection, and not at the upstream administrative tier. It is unlikely that bureaucrats have regular contact with citizens, and any citizen voice would need to be transmitted via “the long route of accountability”—from citizen to politician and then from politician to bureaucrat (World Bank 2003). Asking bureaucrats about their interactions with politicians through surveys, however, is a difficult and sensitive topic, and one that has been broached only cautiously in our work to date. Methodologically, it requires more experimental approaches, which adds complexity to the surveys, and is an ambition for future work.